Binary Mutual Diffusion Coefficients of Aqueous Solutions of Sucrose, Lactose, Glucose, and Fructose in the Temperature Range from (298.15 to 328.15) K - Ribeiro, Ana C. F. (2006)
Binary mutual diffusion coefficients measured by the Taylor dispersion method in two different laboratories (University of Naples, Federico II, Italy, and University of Coimbra, Portugal) are reported for aqueous solutions of lactose, sucrose, glucose, and fructose at various concentrations (0.001 to 0.1) mol·dm-3 and temperatures (298.15 to 328.15) K. The hydrodynamic radius and activation energy for the diffusion of aqueous sugars are calculated from those results. In addition, the measured diffusion coefficients are used with the Hartley equation to estimate activity coefficients for aqueous lactose, sucrose, glucose, and fructose.